2022
DOI: 10.1021/acs.joc.2c00442
|View full text |Cite
|
Sign up to set email alerts
|

Computationally Probing the Mechanism of the Blue-Light-Driven O–H Functionalization of Alcohols by Aryldiazoacetates: Photobasicity or Carbene Chemistry

Abstract: Photochemistry provides green alternatives to traditional reaction conditions and opens up routes toward products that are otherwise difficult to make. Recent work by Koenigs and co-workers demonstrated the blue-light-driven O–H functionalization of alcohols by aryldiazoacetates. Based on spectroscopic and computational analyses, Koenigs and co-workers demonstrated that the alcohols form a hydrogen-bonding complex with aryldiazoacetates prior to the light absorption, with the strength of hydrogen bonding corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
6
0
2
Order By: Relevance
“…52 N–H insertions were reported with amines, 15,43 indoles, 43,53 carbazoles, 43,54,55 pyrazoles, 55 1,2,3-triazoles, 55 amides, 56 sulfonamides, 56 imides, 56 and isatines. 56 O–H insertions were also successfully accomplished with carboxylic acids, 15 perfluorinated alcohols, 57,58 alcohols, 15,59 phenols, 60 oximes, 61–63 hydroxamic acids (generated in situ from a NHC catalyst, aldehydes and nitroso compounds) 64 and phosphinic acids (generated in situ presumably from the air oxidation of H-phosphine oxides). 65 Intriguingly, Koenigs and co-authors had initially proposed that the O–H insertion of more acidic compounds would proceed via a photoinduced proton transfer mechanism, 57,60 which would be an alternative not involving the formation of free carbene intermediates.…”
Section: Donor–acceptor Diazo Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…52 N–H insertions were reported with amines, 15,43 indoles, 43,53 carbazoles, 43,54,55 pyrazoles, 55 1,2,3-triazoles, 55 amides, 56 sulfonamides, 56 imides, 56 and isatines. 56 O–H insertions were also successfully accomplished with carboxylic acids, 15 perfluorinated alcohols, 57,58 alcohols, 15,59 phenols, 60 oximes, 61–63 hydroxamic acids (generated in situ from a NHC catalyst, aldehydes and nitroso compounds) 64 and phosphinic acids (generated in situ presumably from the air oxidation of H-phosphine oxides). 65 Intriguingly, Koenigs and co-authors had initially proposed that the O–H insertion of more acidic compounds would proceed via a photoinduced proton transfer mechanism, 57,60 which would be an alternative not involving the formation of free carbene intermediates.…”
Section: Donor–acceptor Diazo Compoundsmentioning
confidence: 99%
“…Nevertheless, later, the same group and Petit and co-workers have made calculations indicating otherwise: the mechanism for the O–H insertion of several acidic alcohols would involve free carbenes as key reactive intermediates. 58 Similarly, S–H insertions of thiols 30,66 and Si–H insertions of silanes 67 are also possible. The generation of free carbenes can be also strategically employed for the formation of ylides, followed by synthetically useful transformations.…”
Section: Donor–acceptor Diazo Compoundsmentioning
confidence: 99%
“…To test the reactivity of acceptor-only diazo compounds under photochemical reaction conditions, we selected commercially available ethyl diazoacetate 1 as the free carbene precursor (Scheme ). The acidity of the O–H functional group was found to have a significant effect on the product formation . No reaction occurred when benzyl alcohol 2 was used.…”
mentioning
confidence: 95%
“…However, this method is mostly limited to the formation of sulfur ylide intermediates and oxonium ylide intermediates . Compounds containing O–H functional groups often have special reaction properties in the photopromoted conversion of diazo compounds. , For example, under visible-light irradiation, alcohols, oximes, and carboxylic acids can react with aryldiazoacetates through direct O–H functionalization using DCM as solvent (Scheme ). In contrast, when cyclic ethers are used as the reaction media, they often act as nucleophiles and capture the oxonium ylide intermediate generated by the free carbene and cyclic ethers (Scheme ).…”
mentioning
confidence: 99%
“…and Petit's group216 conducted computational studies, which suggested a different mechanism: the O−H insertion mechanism in several acidic alcohols includes free carbenes as essential reactive intermediates.In 2021, Yue, Wei, and co-workers established a photocatalytic method for synthesis of α-ketoesters 101.2 through aerobic oxidation of α-diazoesters 101.1 (Scheme 101) 217. The Scheme 97.…”
mentioning
confidence: 99%